An Efficient Image Quality Enhancement using Wavelet Transform. (2020) - Arunachalaperumal, C.; Dhilipkumar, S.
Abstract: Now a days the internet usage is very high. Similarly, the electronic gadgets like mobile, smart phones etc. usage are very high. Images are sent from one device to other device through internet and the receiver gets the image with poor quality due to high compression rates. Large amount of bandwidth is used for transmitting unstructured data such as images and other files. This large bandwidth usage tends to become a burden for the network and slow down the process. So the optimization takes place. In order to enhance the quality of the image and also reduce the transmission of bandwidth size, a novel image compression technique is proposed in this project. Discrete Wavelet transform is used for image processing and it is planned to use MATLAB. This method provides a compression ratio up to 65% and a PSNR value up to 21.73db.